Assessment of habitat characteristics on wild boar detection in selected forest reserves in Peninsular Malaysia - Ku Halim, Ku Noor Khalidah (2021)
Wild boar (Sus scrofa) populations have increased remarkably worldwide. In predominantly Muslim region such as Peninsular Malaysia, wild boars have thrived, in part, because Muslims do not hunt them as they are prohibited from consuming pork. This is complicated by the decline of predators such as Malayan Tigers. We examined the relationship between the number of wild boar detections, with vegetation structure characteristics, and landscape metrics in 12 forest reserves in Peninsular Malaysia. Camera-trapping was used to record wild boar detections. At each camera trap location, the site-level characteristics and landscape metrics were measured. We found that the number of wild boar detections was 2.5 times higher in Peat Swamp Forest compared to Lowland Dipterocarp Forest. In contrast, the number of wild boar detections was six times lower in Montane Forest compared to Lowland Dipterocarp Forest. The data further revealed that the number of wild boar detections was positively related to the number of trees with diameter at breast height (DBH) > 45 cm, number of fallen trees, number of palms, number of saplings, and elevation. However, the number of wild boar detections was negatively influenced by the number of trees with DBH < 45 cm, canopy cover, distance f rom nearest paved and unpaved roads. Surprisingly, wild boar populations were not af fected by forest f ragmentation and logging. The data indicated that site-level characteristics, particularly vegetation structure, supersede landscape-level characteristics in terms of driving the number of wild boar detections in the forest reserves. The high detection numbers of wild boar may inf luenced by f ive landscape-level characteristics which are number of trees with DBH > 45cm, number of dead fallen trees, number of palms, number of saplings and elevation. Generally, our f indings suggest that wild boars can thrive in tropical fragmented landscapes with favourable site-level characteristics and lower bushmeat hunting pressure.